Peculiarities of the functioning of sacral synonyms (based on the poetic texts of T. Shevchenko) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article deals with the analysis of the functioning of sacral synonyms in the poetry of T. Shevchenko. Synonyms that denominate God and represented by two rows of synonyms – the name of God-Father and God-Son were the object of the research. It is found out that investigated synonyms perform specifying, stylistic and substituting function.
Keywords: synonyms; row of synonyms; functions of synonyms; God; poetry